2021
DOI: 10.3390/ijms222010937
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate Alters Pyruvate Flux and Induces Lipid Accumulation in Cultured Colonocytes

Abstract: Butyrate is considered the primary energy source of colonocytes and has received wide attention due to its unique health benefits. Insight into the mechanistic effects of butyrate on cellular and metabolic function relies mainly on research in in-vitro-cultured cells. However, cells in culture differ from those in vivo in terms of metabolic phenotype and nutrient availability. For translation, it is therefore important to understand the impact of different nutrients on the effects of butyrate. We investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Here, indoxyl sulfate, a gut-derived uremic toxin was used as a representative toxin for the in vitro test in enterocyte cell lines. As such, an impact of butyrate on uremic toxin (indoxyl sulfate)-stimulated enterocytes was demonstrated in vitro (enterocyte integrity and anti-inflammation) along with the increased enterocyte cell energy supporting a previous publication ( 93 ). The administration of butyrate as a chemical drug is interesting due to an easier production process than probiotic preparation; however, the proper dose adjustment will be necessary as butyrate toxicity is possible ( 94 , 95 ).…”
Section: Discussionsupporting
confidence: 84%
“…Here, indoxyl sulfate, a gut-derived uremic toxin was used as a representative toxin for the in vitro test in enterocyte cell lines. As such, an impact of butyrate on uremic toxin (indoxyl sulfate)-stimulated enterocytes was demonstrated in vitro (enterocyte integrity and anti-inflammation) along with the increased enterocyte cell energy supporting a previous publication ( 93 ). The administration of butyrate as a chemical drug is interesting due to an easier production process than probiotic preparation; however, the proper dose adjustment will be necessary as butyrate toxicity is possible ( 94 , 95 ).…”
Section: Discussionsupporting
confidence: 84%
“…In addition to regulating glutamine metabolism, MYC modulates aerobic glycolysis by promoting glucose uptake (by enhancing glucose transporter SLC2A1 expression [95] ), activating the production of pyruvate (by elevating PKM expression [96] ), and modulating lactate export (by inducing lactate transporters-monocarboxylate transporters MCT1 and MCT2 [97] ). First, butyrate treatment increases glucose uptake in Caco-2 cells [98] . In this study, we also observed elevated glucose and altered expression of GLUT genes in SCFA-treated Caco-2 cell lines, including increased insulin-regulated gene GLUT4 ( SLC2A4 ) and decreased expression of non-insulin-dependent genes GLUT2 ( SLC2A2 ) and GLUT9 ( SLC2A9 ), which is in contrast with previous reports on increased gene expression of GLUT2 in SCFA-treated cells [99] , [100] .…”
Section: Discussionmentioning
confidence: 96%
“… 17 In addition, butyrate has been reported to affect cellular metabolic patterns in several cell types, including colonocytes, CD8 + T cells, and CD4 + T cells. 18–20 We then investigated whether butyrate modulates Th1 cell metabolism, especially mitochondrial oxidation and glycolysis, to promote GzmB production. We activated CD4 + T cells with αCD3 mAb and αCD28 mAb under Th1 conditions in the presence or absence of butyrate for 24 h and measured the oxygen consumption rate (OCR), which is primarily attributed to mitochondrial oxidation, and the extracellular acidification rate (ECAR) that represents glycolysis, by using an extracellular flux Seahorse analyzer.…”
Section: Resultsmentioning
confidence: 99%